Effects of fireworks ancient celebrations on atmospheric concentration of particulate matter in Iran. Issue 2 (2nd April 2020) - Oroji, Balal; Sadighzadeh, Asghar; Solgi, Eisa
ABSTRACT: The Chahar-Shanbe Suri culture in Iran is a significant and direct factor leading to air pollution in Iran. This study investigates why and how "Chahar-Shanbe Suri" culture leads to increased air pollution in Iran. Following the fireworks of Chahar-Shanbe Suri in Tehran, Tehran's air quality index increased by a high slope, and the clean condition with the 49 index at 20 pm was unhealthy for all segments of society with a 177 index at 23 o'clock. Of course, according to the data measured in Tehran's air quality assessment stations, the air quality index in the areas of the city has risen above or near 200, which indicates a very unhealthy condition. The results of the SEM-EDS indicated that the PM of fireworks in the area make up the largest proportion of atmospheric particles. The chemical composition of particle was the origin of organic matter and the soot combinations from the combustion of sulfur compounds. The people, governments, and industry should work together to navigate positive initiatives. Public education and media navigation are necessary for dealing with the cultural aspects of environmental pollution and also, the management of celebrating can reduce the impact of fireworks on the air quality.